Efektivitas Pop Up Flip Book Terhadap Pengenalan Kosa Kata Bahasa Inggris di Taman Kanak-kanak Annisa Kota Sungai Penuh - Melinda, Sonia; Muryanti, Elise (Generasi Emas, 2023)
Language is a communication tool in the shape of a system of sound symbol that is used to interact in a social environment. Pop Up Flipbook is one of the media that can be used to introduce language to early childhood. This research purpose to reveal the effectiveness of using Pop up flipbook media in introducing English vocabulary to children at Annisa Kindergarten, Sungai Penuh City. The research sample was children at Annisa Kindergarten in Sungai Penuh City as many as 20 children consisting of 10 children in the class for experimental and in the class for control. This research design is a quasi-experimental research using pre-test and post-test group control. In this research, the techniques for data collection are experiments and observations. Testing the research instrument quality by validating it with professional judgment and seeing the results using SPSS 20 using the Cronbach Alpha technique. Hypothesis testing uses T-test statistical techniques by SPSS 20 for windows which shows a level in significant. The research results was done in the shape of an effect size of 1,83 were concluded included in the category in high, so that the use of Pop Up Flipbook media in the introduction of English Vocabulary was effective.